Synthesis of Oxazinanones: Intramolecular Cyclization of Amino Acid-Derived Diazoketones via Silica-Supported HClO4 Catalysis - Gallo, Rafael D. C.; Campovilla Jr., Orlando C.; Ahmad, Anees; Burtoloso, Antonio C. B. (Frontiers in Chemistry, 2019)
A Brønsted acid catalyzed intramolecular cyclization of N-Cbz-protected diazoketones, derived from α-amino acids, is described. The reaction proceeds under metal-free conditions and is promoted by ecofriendly silica-supported HClO4 as the catalyst and methanol as the solvent. This transformation enables the short synthesis of various 1,3-oxazinane-2,5-diones under mild reaction conditions and in good yields (up to 90%). The set-up is very simple; by just mixing all reagents together with no work-up necessary before purification, this protocol takes a greener approach.